Diversity and distribution of crustaceans from 13 sheltered sandy beaches along Sao Sebastiao Channel, south-eastern Brazil - Nucci, P. R.; Turra, A.; Morgado, E. H. (Cambridge University Press, 2001)
The crustacean species composition in the intertidal zones of 13 sheltered unconsolidated marine beaches in south-eastern Brazil is described. Fifty-three crustacean species were collected, adding 46 species to the total reported by previous studies in the same region. Decapods dominated the community, in contrast to exposed sandy beaches where peracarids normally predominate. The species were distributed irregularly among the beaches. Richness varied markedly among sites, and was positively related to a combination of factors such as fine sand grains, high organic matter content, and relatively low silt-clay content. The presence of rock fragments enabled both rocky shore and sandy beach crustaceans to occur oil the same beaches. Richness and abundance of crustaceans showed no clear relationship to sediment grain size and slope, in contrast to the norm for exposed sandy beaches. The dominance of the tanaid Kalliapseudes schubarti in sonic areas may be a result of organic matter pollution in the region. These beaches showed higher species richness than typical sheltered and exposed sandy beaches, indicating that this sheltered, highly heterogeneous seascape is an important area for conservation.